2018
DOI: 10.2147/ahmt.s180489
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vancomycin resistance among isolates of enterococci in Iran: a systematic review and meta-analysis

Abstract: IntroductionEnterococcus is responsible for 10% of hospital-acquired infections. The purpose of this review was to evaluate the prevalence of vancomycin-resistant Enterococcus (VRE) isolates in Iran using a meta-analysis method.Materials and methodsIranian databases, including Magiran and IranDoc, and international databases, including PubMed and MedLib, were examined carefully, and a total of 20 articles published between 2000 and 2011 were extracted. The data were subjected to meta-analysis and random-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
13
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 36 publications
7
13
3
Order By: Relevance
“…Therefore; the pooled prevalence of VRE in Ethiopia was estimated at 14.8%. This estimate is comparable with reports from Iran (14,18.75%) [50,51].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore; the pooled prevalence of VRE in Ethiopia was estimated at 14.8%. This estimate is comparable with reports from Iran (14,18.75%) [50,51].…”
Section: Discussionsupporting
confidence: 90%
“…Our analysis showed that there was a profound increase of vancomycin resistance in E. faecium blood isolates between 2012 (8.1%) and 2018 (19.0%) in EU/ EEA countries (including the United Kingdom). Despite this increase, the 2018 mean VREFm proportion in Europe is still lower than current data reported from other parts of the world, such as the United States (66%) [28], Australia (47%) [7] and countries from the Eastern Mediterranean region such as Iran [29][30][31]. However, VREFm proportions reported in this study are significantly higher than those observed in Chinese hospitals, where VRE rates of lower than 2% were observed [32][33][34].…”
Section: Discussioncontrasting
confidence: 59%
“…This indirectly indicates the potential existence of VRE, not only in health care settings but in in the environment as well as animals in Nigeria, and its likely spread to communities unless properly contained. Our estimate is comparable with reports from Malaysia 25% [ 37 ] but higher than those reported in Ethiopia 14.8% [ 16 ], Iran 14%, 18.75% [ 38 , 39 ], North America (21%), Asia (24%), Europe (20%) [ 40 ], Germany (9.8%) [ 41 ], Iran (9.4%) [ 42 ], the United Kingdom (9.2%) [ 43 ], and Singapore (9.3%) [ 44 ]. Our estimate was probably higher because our studies included animal and environmental sources in addition to clinical settings unlike all the studies listed above where they largely centred on clinical settings.…”
Section: Discussionsupporting
confidence: 88%